Analisis Perilaku Tiang Tunggal Akibat Beban Aksial Tekan Dengan Metode Empirik Dan Elemen Hingga - M. Gevin Ardi; M. Yusa; S. A. Nugroho (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The purpose of this research is to analyse the behavior of single piles under axial compressive load, as far as settlement, load transfer mechanism, and static loading test are concerned. It includes a literary review of two elastic theory-based methods, the Poulos and Davis method and the Randolph and Wroth method, as well as axisymmetric elastic modelling using the finite element-based program Optum G2. The result given by each method are organized in dimensionless charts of settlement and proportion of load transferred to the pile base in terms of the pile slenderness ratio and soil inhomogeneity and the load in terms of the pile settlement and compared amongst each other. This reseacrh also studies axisymmetric elastoplastic modelling in Optum G2, considering the Mohr-Coulomb failure criterion. The case study of the simulation static load test performed on test pile. The soil parameters are got of some project in Riau Province. Althought limited information is available regarding the geological and the geotechnical conditions of the site, the overall results were quite satisfactoryKeywords : pile, axial, elastic method, finite element